Multiscale responses to combined drought and salinity stress in Apocynum: a model for climate-smart dryland restoration - Shoukat, Muhammad Rizwan; Jiang, Li; Buttar, Zeeshan Ali; Tanveer, Mohsin (Frontiers in Plant Science, 2026)
Climate change is intensifying the frequency and co-occurrence of abiotic stresses such as drought and salinity, posing serious challenges to crop productivity and ecosystem stability. Traditional research has largely focused on single-stress responses, leaving significant gaps in our understanding of plant resilience under combined and sequential stressors. Species of the genus Apocynum, particularly Apocynum venetum L. and Apocynum pictum Schrenk are naturally adapted to arid and saline environments and offer a valuable model for studying multistress tolerance in non-model species. This review integrates current insights into the morphological, physiological, biochemical, and molecular responses of Apocynum under concurrent drought and salinity conditions. Key mechanisms include osmotic adjustment, ion compartmentalization, antioxidant enzyme activation, and stress-induced gene expression involving heat shock transcription factors (HSFs), WRKY transcription factors, NAM, ATAF1/2, and CUC2 transcription factors (NAC), mitogen-activated protein kinase (MAPK) cascades, and flavonoid biosynthesis genes such as Apocynum venetum flavanone 3-hydroxylase (AvF3H), flavonoid 3′-hydroxylase (AvF3’H), and flavonol synthase (AvFLS). Additionally, the review highlights the emerging role of stress signaling molecules and phytohormones such as abscisic acid, salicylic acid, and methyl jasmonate in coordinating systemic responses to multiple stressors. Beyond stress resilience, Apocynum species provide ecological services including phytoremediation, carbon sequestration, sand dune stabilization, and microbial community restoration. These traits align closely with global restoration goals and support Sustainable Development Goals (SDG) 13 (Climate Action) and 15 (Life on Land). Given their low-input cultivation requirements and multistress tolerance, Apocynum species hold promise as climate-smart crops for restoring productivity and resilience in degraded dryland systems. Positioning Apocynum as a dual-purpose species that delivers both ecological restoration and crop value can guide the integration of stress-adaptive plants into sustainable agricultural systems under a changing climate.